Creating a community of grace: A history of the Pus&dotbelow;t&dotbelow;i Marga in northern and western India (1493--1905) - Saha, Shandip (University of Ottawa (Canada), 2004)
This thesis will seek to explore the dynamics of religious patronage in colonial and pre-colonial India by tracing the history of a religious community from Western India called the Pus&dotbelow;t&dotbelow;i Marga. This community was founded in North India by the sixteenth century philosopher Vallabha, but by the nineteenth century, the spiritual leaders of the community had become wealthy, affluent landowners who ruled over their own private estates in the state of Rajasthan. This was largely due to the generous patronage that came from members of the Indian mercantile community as well as from members of both the Muslim and Hindu nobility. This thesis will argue that the patronage of this community by both Hindu and Muslim nobility was, in part, rooted in the common assumption of rulers that patronage of religious communities was not only religiously meritorious, but also essential to the craft of state-building, and to maintaining social stability, and social prestige. The relationship dynamics between the religious leaders of the Pus&dotbelow;t&dotbelow;i Marga and its patrons, however, was constantly fluctuating. Mercantile patrons, royal patrons, and spiritual leaders were all socially influential people, but neither exercised absolute dominance over the other. The balance of power constantly shifted between the three groups making it difficult to clearly define the relationship between the community's religious leaders and their supporters.
Keywords: Religion, History of.